Molecular Bases for the Regulation of Adventitious Root Generation in Plants - Li, Shi-Weng (Frontiers in Plant Science, 2021)
The formation of adventitious roots is an ecologically and economically important developmental process, and it is the most important method of vegetative propagation in plants. This review focuses on recently identified genes that regulate the induction and initiation of adventitious roots (ARs) and offers an analysis of this process at the molecular level. The most important genes specifically involved in adventitious rooting are the auxin signaling-responsive genes, including the AUXIN RESPONSE FACTOR (ARF) and the LATERAL ORGAN BOUNDARIES-DOMAIN (LOB) gene families, and genes associated with auxin transport and homeostasis, the maintenance of the quiescent center (QC), and the initiation of the root apical meristem (RAM). Several genes involved in cell wall modulation also regulate adventitious rooting. Furthermore, genes that play roles in the ethylene, cytokinin, and jasmonic acid signaling pathways are also involved in the regulation of adventitious rooting. The cross-talk among these pathways generates a complex network that regulates adventitious rooting